How Student Learn Ohm Law in The Classroom - *, Sarwanto; Sunarno, Widha; Yusliana, Elvin (Proceeding of International Conference on Teacher Training and Education, 2016)
Most of Indonesian Physics teachers begin to teach dynamic electricity with explain the meaning of electric current, ohmâs law, a parallel series circuit, continuing with the example problems, provide practice answer-questions, ending with examination. This study aims to analyze how to learn ohmâs law on student learning with this traditional approach and problem based learning approach. This research method is descriptive analytic study, with a sample of first-year students at the college. In traditional approach student can solve the problem in low order thingking skills but not in high order thingking skills. Student who learn with problem based learning can demonstrate their skill in thingking and psychomotor. It shows students how to think is partial, view of the symptoms considered only on the symptoms. The mindset of the students has been changed into a more holistic when the research data analyzed simultaneously by using linear regression.